Protótipo de um sistema mexedor aplicado no melhoramento do desempenho de corrosão de placas de circuito impresso - Oliveira Júnior, José Ailton de (Universidade Federal Rural do Semi-Árido, 2018)
Corrosion of printed circuit boards is a fundamental part of the process of making the printed circuit boards used, and it is necessary to make them as simple as possible. The present work aims to propose a prototype on the development with the use of devices such as microcontroller and other equipment. The design is aimed at handling a variable temperature while controlling the temperature in a way that maximizes, within limits, the corrosion of printed circuit boards without damaging the board's dielectric and track. The development of body work, heating system, heating system and speed and temperature control. Presentation, tests and experiments according to the performance with the different situations, that cause improved results gradually. Based on previous results, considering a careful selection according to the project, a feasibility of project application is examined. It was found that the increase in temperature and agitation, resulted in a higher speed of corrosion.
Monografia
Keywords: Placas de Circuito; Corrosão; Mexedor; Controle de temperatura; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA